Case-control study of seropositivity for cysticercosis in Cuenca, Ecuador - Goodman, K. A (1999)
The prevalence of neurocysticercosis has been well documented in rural communities in Latin America using the enzyme-linked inmmunoelectrotransfer blot (EITB) assay. We studied the prevalence of neurocysticercosis in an urban, upper-middle class population in Cuenca, Ecuador. Family members of 34 index cases with parenchymal neurocysticercosis on a computed tomography (CT) scan and family members of 14 patients who had normal CT scans after a trauma or migraine were enrolled in the study. Serum was obtained from 226 individuals, 173 (72%) from the case families and 67 (28%) from the control families. Twelve percent of the case family members and 4% of the control family members were seropositive by the EITB assay. This was a statistically significant difference (P , 0.05) when age and education were held constant by logistic regression. Seropositivity was not related to age. No neurologic symptom proved predictive of serostatus and the only demographic variable that correlated with seropositivity was increased crowding. Positive serology in index cases did correlate with CT findings as follows: 86% of patients with active lesions, 67% with transitional lesions, and only 41% of patients with inactive lesions were positive by the EITB assay. Eighteen percent of family members with a positive EITB test result had parenchymal lesions on a subsequent CT scan. This study demonstrates a high rate of seropositivity of cysticercosis among urban, middle to upper-middle class individuals in a region endemic for Taenia solium. Household contacts of patients with neurocysticercosis had a three-fold higher risk of positive serology for cysticercosis, in comparison with controls.